STUDENTS’ READING ACHIEVEMENT TROUGHTHINK-ALOUD-STRATEGY - Pohan, Albert Efendy (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The research is done in order to measure the effect of think aloud strategy toward the students’ reading achievement of eight grade students of SMPN 9 Batam. As we know, that reading ability is very needed, in order to get information as much as possible. Readers in general and also students still think aloud strategy is boring activity, especially in english. The causes are because, they feel hard to understand and get the main point from the reading passage. The method in this thesis is experimental method. The writer does some experimental to prove the influence of think aloud strategy to increase the students ability in reading. As the population, the writer takes eight grade students of SMPN 9 Batam. And as the sample, the writter takes 80 students, which is devided into two groups, 40 students as a control group and 40 students as an experiment group. There are two kinds of test, they are pre-test and post-test. After analizing the data, the writer got that there is a significant differences between the two group test result, it is proved that think aloud strategy is effective to students’ reading achievement.Keywords:Think Aloud Strategy, Reading Achievement